Corporate real estate research: authors, outlets and research priorities - Ramushu, Boitumelo (My University, 2021)
The purpose of this paper is to examine the existing literature pertaining to the ranking of authors, outlets, and research priorities, and the various available methodologies in literature that lend themselves useful to this ranking task, in order to catalogue a pecking order of corporate real estate research. Using a four-pronged literature review process as part of the examination; Identification, Screening, Eligibility and Included Papers (articles), real estate research papers in a wide variety of internationally renowned research outlets, were selected for further analysis. The selected papers were examined using content analysis and summarized using narrative synthesis. Despite the realization of how important corporate real estate is, as per the findings of Zeckhauser & Silverman (1983), there continues to be minimal coverage of corporate real estate research in mainstream journals. Only 7% of the 5 718 articles published in ten (10) journal outlets addressed issues relating to corporate real estate during the period 1990 – 2019. In single-authored articles, Barry P. Haynes leads the ranks with 5 articles, whilst Christopher Heywood led the charge with 13 co-authored articles over the past 30-year period. In relation to institutions affiliated with single-authored articles, Jones Lang LaSalle and Sprint Corporation jointly lead the industry in CRE literature with 5 articles and the National University of Singapore leads the academic institutions with nine (9) articles associated with the university. In terms of affiliations to co-authored articles, Delft University of Technology in the Netherlands led the ranking with twenty-eight (28) articles linked to the university, and again, Jones Lang LaSalle (14)was ranked top in the co-authorship of CRE research in corporate institutions. Lastly, twenty- one (21) countries were linked to 149 single-authored articles and Thirty-two (32) countries were affiliated to 358 co-authored articles. Forty-eight percent (48%) of single-authored articles came out of the U.S.A., The U.S.A. also ranked top in terms of affiliated co-authored articles with 106 articles. There were nineteen (19) themes collectively identified during the period with three (3) main themes dominating article content during the 30-year period. The three themes encapsulated the gist of discussions held under the review period. The “Physical workplaces vs Traditional workspaces vs Virtual environment - New Ways of Working” theme had the most number articles over the period (760 keywords), followed by the “Asset Management Function” (559 keywords), and lastly the “Corporate functions, Strategies, Management, and Leadership Tools” (405 keywords). The current study summarizes key indicators that allow an evaluation of the state of the body of knowledge to academics looking to initiate or continue studies in corporate real estate management. It also provides guidance to industry on where to look for thought leadership in corporate real estate research
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Building, 2021